Legal Protection Of The Creator Of Online SKCK Computer Programs Which Hasn't Be Registered Under Law Number 28 Year 2014 - Ariefzani, Tassaufi; Sutrisno (VJJ, 2019)
Copyright is one part of intellectual property that has the broadest scope of protected objects, because it includes science, art and literature (art and literary) which includes computer programs. Copyright is a special right for the creator or recipient of the right to announce or reproduce the copyright or give permission for it in the fields of science, art, and literature, with certain restrictions. In Article 1 point 1 of Law No. 28 of 2014 concerning Copyright (hereinafter abbreviated as UUHC) it is regulated that copyright is the exclusive right of the creator which arises automatically based on the declarative principle after a work is realized in real form without reducing restrictions in accordance with statutory provisions - invitation. Anform of legal protection for creators of SKCK computer programs online unregistered, that computer programs are including works protected by law. The creator has an exclusive right that is moral rights and economic rights, and the rights are published since an idea is realized in a tangible form, copyright occurs not because of registration of the creation. The creator has the right to obtain proactive and repressive legal protection for the work if the rights are violated. The legal strength of theSKCK computer program online that has not been registered under Law No. 28 of 2014, that the registration of a work is not a requirement and for registrants to be considered as the creator, but if a work is transferred and the transfer of the work is not made in writing as referred to in Article 16 paragraph (2) letter e UUHC, then because it is a must, the transfer of copyright without being made in writing, either under the deed of hand or an authentic deed, is considered to have never occurred a transfer of copyright and there is no written evidence if disputed on the basis of copyright infringement.